Identifying RO9021 as a Potential Inhibitor of PknG from Mycobacterium tuberculosis: Combinative Computational and in Vitro Studies - Arica-Sosa, Alicia (2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb). Despite being considered curable and preventable, the increase of antibiotic resistance is becoming a serious public health problem. Mtb is a pathogen capable of surviving in macrophages, causing long-Term latent infection where the mycobacterial serine/threonine protein kinase G (PknG) plays a protective role. Therefore, PknG is an important inhibitory target to prevent Mtb from entering the latency stage. In this study, we use a pharmacophore-based virtual screening and biochemical assays to identify the compound RO9021 (CHEMBL3237561) as a PknG inhibitor. In detail, 1.5 million molecules were screened using a scalable cloud-based setup, identifying 689 candidates, which were further subjected to additional screening employing molecular docking. Molecular docking spotted 62 compounds with estimated binding affinities of-7.54 kcal/mol (s.d. = 0.77 kcal/mol). Finally, 14 compounds were selected for in vitro experiments considering previously reported biological activities and commercial availability. In vitro assays of PknG activity showed that RO9021 inhibits the kinase activity similarly to AX20017, a known inhibitor. The inhibitory effect was found to be dose dependent with a relative IC50value of 4.4 ± 1.1 μM. Molecular dynamics simulations predicted that the PknG-RO9021 complex is stable along the tested timescale. Altogether, our study indicates that RO9021 is a noteworthy drug candidate for further developing new anti-TB drugs that hold excellent reported pharmacokinetic parameters.